Identification of Enzymes from Pseudogluconobacter saccharoketogenes Producing d-Glucaric Acid from d-Glucose. Issue 1 (20th October 2021) - Ito, Tetsuya; Masaki, Hisaharu; Fujita, Koki; Murakami, Hiromi; Shizuma, Motohiro; Kiso, Taro; Kiryu, Takaaki
ABSTRACT: In 2004, the US Department of Energy listed d -glucaric acid as one of the top 12 bio-based chemicals and a potential biopolymer building block. In this study, we show that Pseudogluconobacter saccharoketogenes strains can produce d -glucaric acid from d -glucose, although in low yield because of the generation of the byproduct 2-keto-d -gluconic acid in large quantities. To improve d -glucaric acid yield, we generated Rh47-3, a P. saccharoketogenes IFO14464 mutant, which produced d -glucaric acid from d -gluconic acid and d -glucose with 81 and 53 mol% yields, respectively. Furthermore, the key enzymes involved in d -glucaric acid production, alcohol dehydrogenase (Ps-ADH), aldehyde dehydrogenase (Ps-ALDH), and gluconate 2-dehydrogenase (Ps-GADH), were purified and their roles in d -glucaric acid synthesis were evaluated. Ps-ADH and Ps-ALDH catalyzed d -glucaric acid production, which was mediated by d -gluconic acid and d -glucuronic acid pathways. In contrast, Ps-GADH inhibited d -glucaric acid production by promoting the formation of 2-keto-d -gluconic acid from d -glucose. Graphical Abstract: